A Need to Spread Awareness to Slums in Chennai About the Pandemic Covid-19 - A Review. - PRADEEP, RAJASRI; ANJALI, DR A.K; DR MURALIDHARAN (The journal of contemporary issues in business and government, 2020)
The Coronavirus disease 2019 pandemic is very worrying for global public health. This pandemic fallout highlights how the failure in the urban ruling caused a social impact of threats facing the world. Despite all the threats, the well to do urban settlements manage to get through the difficulties with public benefits, education, and all other necessities of life and despite this progress seen in humanity, slum dwellers lack even the most basic public services i.e access to clean water and sanitation. Such unsanitary conditions due to failure of extension of cleaning sewage in clustered slum areas like in Chennai, the COVID-19 will take a toll and lead to massive community spread. The congestion has currently led to an easy spread and if not controlled by the people themselves with precautionary measures, the disease rate may doubly rise. It is therefore very much necessary to spread awareness regarding the massive pandemic COVID -19 to slums in Chennai as the control of the spread becomes impossible without each and everyone's support.